Development and Implementation of Innovative Technologies That Ensure an Increase in The Extraction of Non-ferrous, Noble, Rare, Rare-Earth Metals - Kenzhaliyev, Bagdaulet Kenzhalievich; Arkad’yevich, Kvyatkovskiy Sergey; Anatolyevich, Trebukhov Sergey; Abdulvaliyev, Rinat Anvarbekovich; Koizhanova, Aigul; Tussupbayev, Nessipbay Kuandykovich; Gladyshev, Sergey Vladilenovich; Kassymova, Gulzhaina K. (Teknomekanik, 2022)
The article presents the most innovative technologies developed by Satbayev University, "Institute of Metallurgy and Ore Beneficiation" JSC (Republic of Kazakhstan, Almaty) in recent years. The implementation of these works on an industrial scale will lead to significant economic and environmental effects. The following technologies are described: synthesis of a new foaming agent for intensification of flotation enrichment of gold-bearing ores; multicomponent microflotation, which allows to increase the extraction of valuable metals at existing deposits and to develop new, relatively poor and previously economically unpromising deposits; flotation enrichment of persistent gold-containing ore; contractile pyrometallurgical selection, which allows direct melting of persistent gold-containing raw materials with the transfer to the gas phase of arsenic, sulfur and other volatile components, followed by their neutralization and concentration of gold, silver and other non-ferrous metals in matte melt; continuous conversion of copper matte in the Vanyukov furnace; processing of liquid metallurgical slags in a furnace with an electrically heated coke filter; vacuum distillation refining of rough selenium; extraction of rare earth metals from extraction phosphoric acid obtained during the processing of phosphorites; processing of high-grade low-quality bauxite.